Proceedings of ICEPP 2021 Efficient Production and Processing - Vankov, Yury.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book gathers the latest advances, innovations, and applications in the field of environmental and construction engineering, as presented by international researchers and engineers at the 2nd International Conference on Efficient Production and Processing, held on February 25-26, 2021. It covers highly diverse topics, including use of secondary raw materials in construction technologies; urban waste management logistics; use of recycled materials in road construction; safety and security in waste handling; food science and agriculture; waste and water treatment; and environmental economics. The contributions, which were selected by means of a rigorous international peer-review process, highlight numerous exciting ideas that will spur novel research directions and foster multidisciplinary collaborations.
Chapter 1: High-frequency drying processes simulation of wooden tangent towers in a vacuum chamber -- Chapter 2: 003 Anti-crisis marketing at the enterprises of the energy complex in a new reality -- Chapter 3: Analysis of Digital Intellectual Devices Functioning under Electromagnetic and Electromechanical Transient Processes in Power Systems -- Chapter 4: Energy efficiency analysis of control algorithms for fan electric drives in gas air-cooling plants -- Chapter 5: Improving the environmental performance of the diesel engine (21/21) by upgrading the fuel supply system -- Chapter 6: A method for generating a digital twin model of a power parameter control system based on a dynamic Descartes square deviation graph -- Chapter 7: Scientific-methodological apparatus for construction of monitoring systems by power networks of intellectual buildings and systems -- Chapter 8: Increasing The Efficiency Of Cooling Water Resources Using At Power Plants.
Keywords: Refuse and refuse disposal; Construction industry -- Management; Environmental economics; Food science; Waste Management/Waste Technology; Construction Management; Environmental Economics; Food Engineering; Manufacturing processes -- Congresses; Production engineering -- Congresses